27-6z=-5(7z-9)

Simple and best practice solution for 27-6z=-5(7z-9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 27-6z=-5(7z-9) equation:


Simplifying
27 + -6z = -5(7z + -9)

Reorder the terms:
27 + -6z = -5(-9 + 7z)
27 + -6z = (-9 * -5 + 7z * -5)
27 + -6z = (45 + -35z)

Solving
27 + -6z = 45 + -35z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '35z' to each side of the equation.
27 + -6z + 35z = 45 + -35z + 35z

Combine like terms: -6z + 35z = 29z
27 + 29z = 45 + -35z + 35z

Combine like terms: -35z + 35z = 0
27 + 29z = 45 + 0
27 + 29z = 45

Add '-27' to each side of the equation.
27 + -27 + 29z = 45 + -27

Combine like terms: 27 + -27 = 0
0 + 29z = 45 + -27
29z = 45 + -27

Combine like terms: 45 + -27 = 18
29z = 18

Divide each side by '29'.
z = 0.6206896552

Simplifying
z = 0.6206896552

See similar equations:

| X*2X=166 | | -16=4y-9 | | 2(8b+2)-1+4g-(2-5g)= | | -x-7=x+1 | | x=160-(170-x) | | 43=3u-11 | | x^3-12x^2-6x-12=0 | | 33b-23=b | | 29-5x=9-7x | | 12A-7=-1 | | y=0.15x+0.15 | | 7-4a=2a+2-5a | | 12=6-2y | | y-1=1/5(x-3) | | solvingx^3-12x^2-6x-12=0 | | -7-x=1+x | | -(7-7a)+4a=-23+3a | | 20x^2(-3+4x)=0 | | 1/3x-5/6x=17 | | 157=11-w | | 21x+42=-3 | | 2b^2+5b-62=0 | | 4x-11=3x+3 | | 7-g=-11 | | Y=5/2-20 | | 17j-13j=16 | | 6x+8y=480 | | 2-(6x-19)=7(x-2) | | 6x=6(x+5)+6 | | 4x-8=4x+9 | | 4=-2x+36 | | 7.4x-1.1=13.7 |

Equations solver categories